Screening and Distribution of Contaminants of Emerging Concern and Regulated Organic Pollutants in the Heavily Modified Guadalhorce River Basin, Southern Spain. - Llamas Dios, Marta Inés; Vadillo-Pérez, Iñaki; Candela, Lucila; Jiménez-Gavilán, Pablo; Corada Fernández, Carmen; Castro Gámez, Antonio Fermín (MDPI, 2020)
Emerging pollutants have aroused an increasing concern due to their ubiquitous presence in the environment and harmful potential. Both emerging (e.g., pharmaceuticals and personal care products) and regulated organic pollutants pose a serious threat to water quality and their presence and spatial distribution are complicated to address as they can derive from several factors: distribution of point and diffuse sources, environmental conditions, hydrogeological features of the region and inherent properties of the considered contaminants. In this study, a ground and surface water monitoring campaign was conducted in the three main detritic groundwater bodies of an extensive and heavily modified river basin in order to draft an initial description of the occurrence and distribution of a wide range of organic contaminants. In total, 63 out of 185 target pollutants were detected. An attempt to understand the importance of different factors governing the distribution of some of the most frequently found pollutants was made. Antibiotics spatial distribution is potentially influenced by the hydrogeological functioning of the basin modified by hydraulic infrastructures (reflected by hydrochemistry and environmental tracers δ2H and δ18O), not directly related to the distribution of potential sources. The presence of other organic pollutants does not reflect an evident correlation with flow pathways. Differences in contaminant occurrence are potentially attributed to the way pollutants are released into the environment as well as physico-chemical properties.
Keywords: Aguas subterráneas; Agua - Contaminación; Indicadores ambientales; Contaminantes orgánicos del agua; Ecología de ríos; Emerging contaminants; Organic contaminants; Groundwater; Environmental tracers; Large scale